Significance of laboratory markers in the diagnosis and postoperative monitoring of patients with medullary thyroid cancer - L. A. Ivanova; O. N. Rostovtseva; L. S. Malygina; A. N. Pakhomova; J. M. Gavrilova; A. S. Klimova (Кубанский научный медицинский вестник, 2014)
The histologic picture of the medullary cancer can resemble a papillary and follicular cancer that takes away doctors towards the wrong statement of the diagnosis. Therefore it is necessary to investigate calcitonin in the presence of knot in a thyroid gland. Research on existence of mutation RET-protoonkogen is obligatory for an exception of hereditary forms of the medullary cancer. Research of time of doubling of calcitonin in the postoperative period allows to predict survival of patients. Bisfosfonates interfere with progressing of metastatic process at the medullary cancer of the thyroid gland.